Karakteristik Pemilihan Jarak Penyebab Bangkitan Perjalanan Mahasiswa Pengguna Sepeda Motor (Studi Kasus Mahasiswa Teknik Sipil Universitas Syiah Kuala) - Nanda, Gebrina Rizki; Angggraini, Renni; Sugiarto, Sugiarto (Journal of The Civil Engineering Student, 2025)
The need for movement of activities in Banda Aceh City can lead to a revival of movement. Motorcycles are the most widely used modes of society, especially students to fulfill their activities. The rise of high movement will interfere with the existing transportation infrastructure system. Therefore, it is necessary to analyze the characteristics of the rise of motorcycle users which is reviewed based on one of the movement characters that is the distance of travel. The purpose is to see the factors that influence the rise both based on home based and non home based and also to know the magnitude of the probability that occurs due to distance. This research is focused on Civil Engineering students of Unsyiah who have an active force status. The samples taken amounted to 220 out of 488 population. The method used is Discrete Choice Model with approach model Multinomial Logit, so there are 3 alternative choice that is distance 3 km, 3-6 km and 6 km. The model parameters were estimated with SPSS 2.1 software which resulted in the utility equation and then the influential variables and probabilities will be obtained.